Wavefront‐sensorless adaptive optics with a laser‐free spinning disk confocal microscope. (20th November 2020) - Hussain, Syed Asad; Kubo, Toshiki; Hall, Nicholas; Gala, Dalia; Hampson, Karen; Parton, Richard; Phillips, Mick A.; Wincott, Matthew; Fujita, Katsumasa; Davis, Ilan; Dobbie, Ian; Booth, Martin J.
Abstract: Adaptive optics is being applied widely to a range of microscopies in order to improve imaging quality in the presence of specimen‐induced aberrations. We present here the first implementation of wavefront‐sensorless adaptive optics for a laser‐free, aperture correlation, spinning disk microscope. This widefield method provides confocal‐like optical sectioning through use of a patterned disk in the illumination and detection paths. Like other high‐resolution microscopes, its operation is compromised by aberrations due to refractive index mismatch and variations within the specimen. Correction of such aberrations shows improved signal level, contrast and resolution.